The Impact of Clinical Pharmacist Consultation on the Treatment of Multi-Drug Resistant Organisms (MDRO) Infections: A Retrospective Observational Study - Fang F; Zhai X; Bao S; Fan X; Bai R; Ma Y; Dong X (Journal of Multidisciplinary Healthcare)
Fang Fang, Xiaobo Zhai, Siwei Bao, Xiucong Fan, Rong Bai, Yabin Ma, Xiaohui Dong Department of Pharmacy, Affiliated Shanghai East Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of ChinaCorrespondence: Xiaohui Dong, Department of Pharmacy, Affiliated Shanghai East Hospital, Tongji University School of Medicine, 1800 Yuntai Road, Pudong District, Shanghai, 200123, People’s Republic of China, Email dongxiaohui1226@sina.cn Yabin Ma, Department of Pharmacy, Affiliated Shanghai East Hospital, Tongji University School of Medicine, 1800 Yuntai Road, Pudong District, Shanghai, 200123, People’s Republic of China, Email 15021877977@163.comPurpose: Multidrug-resistant organisms (MDROs) infections are associated with high mortality in hospitalized patients. Clinical pharmacists play a crucial role in optimizing anti-infection treatment strategies. This study aimed to evaluate the impact of clinical pharmacist consultation on the treatment of inpatients with MDRO infections.Methods: Patients infected with MDROs who received clinical pharmacist consultation between June 2020 and June 2023 were enrolled. The adoption rate and effectiveness rate of consultation were calculated. Univariate and multivariate logistic regression analyses were conducted to identify factors influencing the effectiveness rate of consultation. Cox regression analysis was employed to estimate the 30-day survival rate post-consultation for patients infected with MDROs, comparing those who adopting pharmacists’ suggestions with those who did not.Results: A total of 620 patients were included. More patients were from the surgical system, especially neurosurgery. The top 3 infection sites were respiratory tract, urinary tract and blood, with prevalent MDROs including Carbapenem-resistant Klebsiella pneumoniae (CRKP), Carbapenem-resistant Acinetobacter baumannii (CRAB), and Carbapenem-resistant Pseudomonas aeruginosa (CRPA). Following the implementation of consultation recommendations, patients exhibited significant reductions in temperatures, inflammatory markers, and Sequential Organ Failure Assessment (SOFA) scores. The adoption and effectiveness rate of consultation were 89.67% and 58.71%, respectively. Multivariate analysis showed that there were significant association of liver dysfunction (adjusted OR = 0.331, 95% CI: 0.217– 0.504), severity of infection (adjusted OR = 0.292, 95% CI: 0.151– 0.562) and adopting pharmacists’ suggestions (adjusted OR = 1.987, 95% CI: 1.126– 3.507) with the effectiveness rate of consultation. Cox regression analysis revealed a significant difference in the 30-day survival rate between MDRO patients who received pharmacist recommendations and those who did not (HR = 0.422, 95% CI: 0.185– 0.963, P = 0.04).Conclusion: Our research indicated that the involvement of clinical pharmacists could be advantageous for patients afflicted with MDRO infections.Keywords: multidrug-resistant organisms, infectious diseases, clinical pharmacists, consultations